Can Antarctic lichens acclimatize to changes in temperature?. (29th November 2017) - Colesie, Claudia; Büdel, Burkhard; Hurry, Vaughan; Green, Thomas George Allan
Abstract: The Antarctic Peninsula, a tundra biome dominated by lichens and bryophytes, is an ecozone undergoing rapid temperature shifts. Such changes may demand a high physiological plasticity of the local lichen species to maintain their role as key drivers in this pristine habitat. This study examines the response of net photosynthesis and respiration to increasing temperatures for three Antarctic lichen species with different ecological response amplitudes. We hypothesize that negative effects caused by increased temperatures can be mitigated by thermal acclimation of respiration and/or photosynthesis. The fully controlled growth chamber experiment simulated intermediate and extreme temperature increases over the time course of 6 weeks. Results showed that, in contrast to our hypothesis, none of the species was able to down‐regulate temperature‐driven respiratory losses through thermal acclimation of respiration. Instead, severe effects on photobiont vitality demonstrated that temperatures around 15°C mark the upper limit for the two species restricted to the Antarctic, and when mycobiont demands exceeded the photobiont capacity they could not survive within the lichen thallus. In contrast, the widespread lichen species was able to recover its homoeostasis by rapidly increasing net photosynthesis. We conclude that to understand the complete lichen response, acclimation processes of both symbionts, the photo‐ and the mycobiont, have to be evaluated separately. As a result, we postulate that any acclimation processes in lichen are species‐specific. This, together with the high degree of response variability and sensitivity to temperature in different species that co‐occur spatially close, complicates any predictions regarding future community composition in the Antarctic. Nevertheless, our results suggest that species with a broad ecological amplitude may be favoured with on‐going changes in temperature. Abstract : Temperature shifts in the Antarctic demand a high physiological plasticity of the local lichen vegetation to maintain their role as key drivers in this pristine habitat. We examined their ecophysiological response in a fully controlled growth chamber experiment simulating a heat wave. Severe effects on photobiont vitality demonstrated that temperatures around 15°C mark the upper limit for the two species restricted to the Antarctic, and only a widespread lichen species was able to recover its homoeostasis. The high degree of sensitivity to temperature in species that co‐occur complicates predictions regarding future community composition in the Antarctic.